EMG FIELD ANALYSIS IN DYNAMIC MICROSCOPIC/NANOSCOPIC MODELS OF MATTER - Fiala, Pavel; Bartušek, Karel; Dědková, Jarmila; Dohnal, Premysl (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2019)
We discuss a numerical model (macro/micro/nanoscopic) to enable more accurate analysis of electro-hydro-dynamic (EMHD) processes in water at the level of atoms. Dedicated experiments have shown that inserting a relatively homogeneous periodic structure (deionized, degassed, or distilled H2O) in a magnetic field will influence the atomic basis, molecules, and relevant bonds. In this context, the present paper focuses on the designing, analysis, and evaluation of the behavior of an extensive system that represents H2O from the microscopic perspective, and it also outlines the properties and changes of the bonds in the examined water samples. Complementarily, a simple example is used to define the results obtained from analyses of the generated spiral static gradient magnetic and non-stationary gradient electromagnetic fields from the frequency range of f = 1 GHz to 10 GHz.